Optimizing Dhuha Lectures in the Islamic Religious Education Tutorial Program to Improve the Religious Character of UPI Students - Nurmani, Balqis; Budiyanti, Nurti; Surahman, Cucu; Yusranti, Muthia; Rosyada, Noer Amrina (TARBAWY: Indonesian Journal of Islamic Education, 2023)
This research aims to find out how understanding, belief in the application of religious values in dhuha lecture activities in improving the religious character of UPI students class of 2021. This research uses a qualitative descriptive approach. The survey subjects in this research were 50 students at the Indonesian University of Education Class of 2021 using a closed questionnaire method. The results of the research show that all survey subjects, namely 50 UPI students class of 2021, that they understand, believe and apply the religious values provided by UPI in the PAI Tutorial dhuha lecture activities. Thus, it can be concluded that all survey subjects, namely 50 UPI students class of 2021, stated that PAI tutorials can educate and provide benefits.